Epigenetic Modifiers to Treat Retinal Degenerative Diseases - Evgenya Y. Popova; Lisa Schneper; Aswathy Sebastian; Istvan Albert; Joyce Tombran-Tink; Colin J. Barnstable (Cells)
We have previously demonstrated the ability of inhibitors of LSD1 and HDAC1 to block rod degeneration, preserve vision, maintain transcription of rod photoreceptor genes, and downregulate transcripts involved in cell death, gliosis, and inflammation in the mouse model of Retinitis Pigmentosa (RP), rd10. To extend our findings, we tested the hypothesis that this effect was due to altered chromatin structure by using a range of inhibitors of chromatin condensation to prevent photoreceptor degeneration in the rd10 mouse model. We used inhibitors for both G9A/GLP, which catalyzes methylation of H3K9, and EZH2, which catalyzes trimethylation of H3K27, and compared them to the actions of inhibitors of LSD1 and HDAC. All the inhibitors are likely to decondense chromatin and all preserve, to different extents, retinas from degeneration in rd10 mice, but they act through different metabolic pathways. One group of inhibitors, modifiers for LSD1 and EZH2, demonstrate a high level of maintenance of rod-specific transcripts, activation of Ca2+ and Wnt signaling pathways with the inhibition of antigen processing and presentation, immune response, and microglia phagocytosis. Another group of inhibitors, modifiers for HDAC and G9A/GLP, work through upregulation of NGF-stimulated transcription, while downregulating genes belong to immune response, extracellular matrix, cholesterol signaling, and programmed cell death. Our results provide robust support for our hypothesis that inhibition of chromatin condensation can be sufficient to prevent rod death in rd10 mice.